The Relevance of Principles of Islamic Education Philosophy in the Context of Education in the 21st Century at SMK IT Khoiru Ummah Curup - Putri Adelia; Rejabil Anbia (Indonesian Journal for Islamic Studies, 2023)
The purpose of the study is to assess the applicability of Islamic educational philosophy at SMK IT Khoiru Ummah Curup in the context of education in the twenty-first century. Education is recognized as a fundamental pillar in shaping the character of individuals and society, with Islamic philosophical principles serving as the foundation for holistic and spiritual learning. Despite the challenges posed by changing times and technological advancements, field research with a descriptive qualitative approach indicates that these principles remain relevant at SMK IT Khoiru Ummah Curup. This research involves fieldwork with a descriptive qualitative approach, using data collection techniques and data validity methods. The findings of the research demonstrate the relevance of this concept, as evidenced by the acknowledgement of the role that tawhid plays in inclusive and tolerant education, the blending of Islamic sciences with contemporary knowledge, the focus on the whole development of students in the technological age, the value placed on high moral standards, and the advocacy for inclusive and tolerant education. for the development of quality individuals who make a positive contribution to society. The simulation that can be taken from this study is that the research findings provide a deep understanding of the relevance of philosophical principles of Islamic education at SMK IT Khoiru Ummah Curup in the 21st century, with practical implications such as curriculum development and teaching methods that are in harmony with the context of modern Islamic education. This is expected to provide benefits for educational institutions in integrating these principles effectively.